Penerapan Teknik Relaksasi Foot Massage Untuk Mengurangi Nyeri Pada Pasien Post Sectio Caesarea Di Bangsal Firdaus PKU Gamping - Gianina Sindi M; Syahruramdhani Syahruramdhani (Jurnal Sains dan Kesehatan, 2023)
Sectio caesarea delivery is a form of labor process that is carried out by making incisions in the abdominal wall and uterine wall to deliver the fetus from the uterus. Patients who give birth by cesarean section method will usually feel various discomforts. One of the discomforts felt is pain originating from an abdominal incision. So we need a management that can reduce complications and improve quality in post partum mothers, namely by doing foot massage relaxation techniques. The purpose of this case study was to determine the effect of foot massage in reducing pain in post-cesarean section patients. This study used a case study method with a nursing care approach, namely taking 1 patient as a descriptive analysis. Methods of data collection by interviews, observation, pre-test, intervention, and post-test. The research was conducted on March 16-18 2023 at the PKU Gamping Firdaus Ward. The results of the case study showed a decrease in the pain scale in post sectio caesarea patients after foot massage was performed. From the results of the case study, it can be concluded that there is a significant effect of foot massage on changes in pain in post-cesarean section patients.